Assistência a recém-nascidos de alto risco: do hospital ao domicílio - Elaine Trevezanuto Correia; Dandara Novakowski Spigolon; Edilaine Maran; Maria Antonia Ramos Costa; Sonia Silva Marcon; Elen Ferraz Teston (Universidade Federal do Ceará, 2019)
Objective to apprehend the perceptions of caregivers of high-risk newborns about care provided by health professionals.Methods a qualitative study with 11 main caregivers of newborns. Data were collected through semi-structured interview, audio recorded, and submitted to content analysis.Results caregivers of high-risk newborns emphasized the reception at birth and information on the health and evolution of the baby during hospitalization and at discharge, as factors that made the difference in the hospital setting. In the context of Primary Care, those that reflected on the safety/trust and satisfaction with the assistance provided were: multi professional care, follow up with the pediatrician in the reference center, home visit and nursing consultation.Conclusion caregivers of high-risk newborns perceived positively the care provided by health professionals, both in the hospital environment and at home.